2016
DOI: 10.1016/j.cub.2016.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Three-Step Model for Polarized Sorting of KIF17 into Dendrites

Abstract: Kinesin and dynein motors drive bidirectional cargo transport along microtubules and have a critical role in polarized cargo trafficking in neurons [1, 2]. The kinesin-2 family protein KIF17 is a dendrite-specific motor protein and has been shown to interact with several dendritic cargoes [3-7]. However, the mechanism underlying the dendritic targeting of KIF17 remains poorly understood [8-11]. Using live-cell imaging combined with inducible trafficking assays to directly probe KIF17 motor activity in living n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…LUHMES differentiation into functional neurons has been described elsewhere and our work faithfully replicated the findings, including the overall time frame (Scholz et al, 2011; Shah et al, 2016; Harischandra et al, 2020). Accordingly, we observed that, in addition to the ciliary marker ARL13B ( Figure 5A ), differentiating LUHMES neurons expressed the general neurite marker tubulin beta 3 (TUBB3) and the synaptic marker post-synaptic density protein 95 (PSD95) ( Figure 5B ), the neuronal transport marker kinesin 17 (KIF17) ( Figure 5C ) as well as tyrosine hydroxylase (TH), the terminal differentiation marker for dopaminergic neurons ( Figure 5D ) (Wulle and Schnitzler, 1989; Lee et al, 1990; Hunt et al, 1996; Franker et al, 2016). The expression of various markers for neuronal differentiation, maturation and function, suggested that our culture conditions successfully induced neuronal differentiation, in accordance with previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…LUHMES differentiation into functional neurons has been described elsewhere and our work faithfully replicated the findings, including the overall time frame (Scholz et al, 2011; Shah et al, 2016; Harischandra et al, 2020). Accordingly, we observed that, in addition to the ciliary marker ARL13B ( Figure 5A ), differentiating LUHMES neurons expressed the general neurite marker tubulin beta 3 (TUBB3) and the synaptic marker post-synaptic density protein 95 (PSD95) ( Figure 5B ), the neuronal transport marker kinesin 17 (KIF17) ( Figure 5C ) as well as tyrosine hydroxylase (TH), the terminal differentiation marker for dopaminergic neurons ( Figure 5D ) (Wulle and Schnitzler, 1989; Lee et al, 1990; Hunt et al, 1996; Franker et al, 2016). The expression of various markers for neuronal differentiation, maturation and function, suggested that our culture conditions successfully induced neuronal differentiation, in accordance with previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, experiments examining the trafficking of full-length Kif-17 identified distinct roles for the two motor proteins (Franker et al, 2016). Actin appears to be involved in halting Kif-17-mediated movement of peroxisomes following entry into the proximal axon, in a manner similar to halting that was observed for vesicles carrying dendritic proteins (Al-Bassam et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, vesicles carrying nonspecifically localized proteins that are induced to interact with Myosin Va halt and reverse. Finally, full length Kif17 localizes to dendrites in part as a result of interaction with the actin cytoskeleton in the proximal axon, which stops its movement into the distal axon (Franker et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The AIS recruits cell adhesion molecules to create a dense membrane protein region to prevent plasma membrane mixing. And the AIS controls entry of axonal cargoes and prevents erroneous entry of somatodendritic vesicles and redirects them back to the cell body (Lewis et al, 2009;Watanabe et al, 2012;Franker et al, 2016;Kuijpers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%